Adaptation Strategies to Improve the Resistance of Oilseed Crops to Heat Stress Under a Changing Climate: An Overview - Ahmad, Muhammad; Waraich, Ejaz Ahmad; Skalicky, Milan; Hussain, Saddam; Zulfiqar, Usman; Anjum, Muhammad Zohaib; Habib ur Rahman, Muhammad; Brestic, Marian; Ratnasekera, Disna; Lamilla-Tamayo, Laura; Al-Ashkar, Ibrahim; EL Sabagh, Ayman (Frontiers in Plant Science, 2021)
Temperature is one of the decisive environmental factors that significantly affect plant growth. Temperatures are projected to increase by 1.5 °C over the next two decades as a result of climate change. Particularly, rising temperatures are severely affecting the growth and development of oilseed crops both yield and quality. Oilseed crops such as soybean, sunflower, canola, peanut, cottonseed, coconut, palm oil, sesame, safflower, olive, etc. are widely grown and of specific importance is dependence of oil synthesis on temperature and water availability, which is threatening the stability of yield and quality. In general, oilseeds show reduced oil contents and food quality at rising temperatures. Thus, a proper understanding of underlying mechanisms of genotype-environment interactions that could affect oil synthesis pathways is a prime requirement in developing stable cultivars. Typically, plants have adapted numerous mechanisms to cope with heat stress, including preservation of membrane integrity, production of heat shock proteins (Hsps), scavenging of reactive oxygen species (ROS), assembly of antioxidants, buildup compatible solutes, altered metabolic processors, and modified gene expressions permitting plants to thrive and survive. Acquiring thermo-tolerance by modern genomics can mitigate the harmful effects caused by heat stress. Manipulation of multiple genes responsible for thermo-tolerance, exploring their high expressions have a great impact on potential application using collective molecular techniques like genomics, transcriptomics, proteomics, metabolomics, ionomics, and phenomics. This review highlights the latest outcomes on the response, and tolerance to heat stress at the cellular, organelles, and whole plant levels describing numerous approaches applied to enhance thermos-tolerance in oilseed crops. We attempt critically analyze the scattered existing thermo-tolerant approaches used in oilseed crops as a whole, directing to extend studies into field and provide beneficial information to researchers and related parties to streamline their breeding programs to explore new ways and develop guidelines to achieve next-generation sustainability under a changing climate.